Seismic Performance Analysis of Buildings Strengthened with X-Bracing Systems under Dynamic Earthquake Loads - Nur Lathifah; Imransyah Idroes; Munirul Hady; Bunyamin Bunyamin; Heru Pramanda (Popular Scientist, 2025)
Indonesia, as an archipelagic country located within the Pacific Ring of Fire, has a high level of vulnerability to earthquakes. However, many buildings in earthquake-prone regions have not yet been optimally reinforced against dynamic seismic loads, thereby posing risks to both safety and structural performance. This study analyzes the structural performance of the Cempaka Lima General Hospital building in Banda Aceh, Aceh, Indonesia, using Simeulue earthquake data as the dynamic load. Simeulue Island experienced several major earthquakes, including the significant events in 2004 and 2012, which highlight the region’s high seismic vulnerability. The objective is to evaluate improvements in stiffness, stability, and seismic performance of the building after the application of X-bracing, and to compare these with its condition prior to reinforcement. The novelty of this research lies in the implementation of an X-bracing system in a hospital building located in a high seismic hazard zone, utilizing local earthquake data to yield more realistic results. The findings indicate that the axial force in the unbraced structure reached 20,714.6 kN, whereas after the addition of bracing it decreased to 20,616.33 kN. The largest base shear with bracing occurred on the first floor, at 6512.97 kN (X-direction) and 6497.5 kN (Y-direction). The maximum displacement without bracing was recorded on the fourth floor at 0.564 mm (X-direction), while in the braced structure the displacement was significantly reduced. The story drift values were also below the limit specified by the Indonesian National Standard, which is 2% of the story height, thus fulfilling seismic performance requirements. These results demonstrate that the use of X-bracing can significantly enhance structural stability and maintain the service performance of hospital buildings in earthquake-prone areas.